Bacillus amyloliquefaciens TL promotes gut health of broilers by the contribution of bacterial extracellular polysaccharides through its anti-inflammatory potential - Li, Shijie; Chen, Pinpin; Li, Qiuyuan; Wang, Xu; Peng, Jintao; Xu, Ping; Ding, Hongxia; Zhou, Zutao; Shi, Deshi; Xiao, Yuncai (Frontiers in Immunology, 2024)
The focal point of probiotic efficacy and a crucial factor influencing poultry cultivation lies in the level of intestinal inflammation. In conventional farming processes, the reduction of intestinal inflammation generally proves advantageous for poultry growth. This study investigated the impact of Bacillus amyloliquefaciens TL (B.A.-TL) on inflammatory factor expression at both tissue and cellular levels, alongside an exploration of main active secondary metabolites. The results demonstrated that broiler feeding with a basal diet containing 4 × 10 9 CFU/kg B.A.-TL markedly enhanced chicken growth performance, concomitant with a significant decrease in the expression of genes encoding inflammatory cytokines (e.g., CCL4, CCR5, XCL1, IL-1β, IL-6, IL-8, LITAF, and LYZ) in jejunum and ileum tissues. The extracellular polysaccharides of B.A.-TL (EPS-TL) exhibited notable suppression of elevated inflammatory cytokine expression induced by Escherichia coli O55 lipopolysaccharides (LPS) in chicken macrophage-like cells (HD11) and primary chicken embryonic small intestinal epithelial cells (PCIECs). Moreover, EPS-TL demonstrated inhibitory effect on NF-κB signaling pathway activation. These findings suggested that the metabolic product of B.A.-TL (i.e., EPS-TL) could partly mitigate the enhanced expression of inflammatory factors induced by LPS stimulation, indicating its potential as a key component contributing to the antiinflammatory effects of B.A.-TL.